Predictive Accuracy of GARCH, GJR and EGARCH Models Select Exchange Rates Application (Global Journal of Management and Business Research, 2012)
Accurate forecasted data will reduce not only the hedging costs but also the information will be useful in several other decisions This paper compares three simulated exchange rates of Malaysian Ringgit with actual exchange rates using GARHC GJR and EGARCH models For testing the forecasting effectiveness of GARCH GJR and EGARCH the daily exchange rates four currencies viz Australian Dollar Singapore Dollar Thailand Bhat and Philippine Peso are used The forecasted rates using Gaussian random numbers are compared with the actual exchange rates of year 2011 to estimate errors Both the forecasted and actual rates are plotted to observe the synchronisation and validation The results show more volatile exchange rates are predicted well by these GARCH models efficiently than the hard currency exchange rates which are less volatile Among the three models the effective model is indeterminable as these models forecast the exchange rates in different number of iterations for different currencies The leverage effect incorporated in GJR and EGARCH models do not improve the results much The results will be useful for the exchange rate dealers like banks importers and exporters in managing the exchange rate risks through hedging
Keywords: Forecasting; GARCH; GJR; EGARCH; exchange rate; volatility; Gaussian distribution